The Characterisation and Development of a New Class of Translation-Initiation Inhibitors - Murtza, Aamina (2020)
This thesis describes synthetic methodologies towards monogalactosyldiacylglycerol and their glycolipid variants, an emerging class of translational inhibitors which show significant potential in eliminating proliferatory disease. The Hayes group have identified MGDG 1, a translation- initiation inhibitor which exerts its therapeutic effects through inhibiting eIF4A, a helicase which functions to unwind RNA in the translational stages of synthesis. However, its specific mode of action and binding has not yet been elucidated.